Commercialization of Hydrogel Fertilizer Slow Release Based on Organic Waste, Microbes, and Mycorrhizal for Floriculture - Rio Kevin Marcello Alwi; Muhammad Samsul Maarif; Eric Verchius; Intan Delia Rustandi; Mentari May Syachanna; Fahrizal Hazra (School of Business, IPB University (SB-IPB), 2022)
Floriculture production and productivity are increasing approximately 27% per year. However, its productivity still faces problems such as unfulfilled nutrients, which overcame by fertilization. Organic fertilizers from banana weevils, tofu pulp, palm liquid waste, and rice water can continuously release macro and micronutrients and increase soil microbes' diversity. Currently, no fertilizer can collect all these benefits, so is present. This activity aims to commercialize Cobio by optimizing the use of organic waste, microbes, and mycorrhizal that compete in the market. The method used is quantitative descriptive as a reference in conducting four stages: the market opportunity projection, the production stage, the marketing and distribution stage, and the evaluation stage. Data obtained after achieving sales targets in July - August 2021 and further September – October 2021 with total products sold reaching 1.263 pcs. In achieving this target, Cobio utilizes social media and marketplaces to communicate with consumers. One of which is WhatsApp Business as a marketing channel with the most significant sales figure of 918 pcs. Cobio's sales distribution has also reached 13 provinces in Indonesia show public interest in this product. Cobio has an R/C value of 1,59, which indicates its future sustainability prospects. Keywords: commercialization, floriculture, hydrogel, mycorrhizal, organic waste